Legal Counseling on the Introduction of Anti-Corruption Values and Village Financial Management - Lewerissa, Yanti Amelia; Hehanussa, Deassy Jacomina Anthoneta (AIWADTHU: Jurnal Pengabdian Hukum, 2026)
Introduction: Eradicating corruption must begin by instilling anti-corruption values in the nation's younger generation. Likewise, an understanding of village financial management, including Village Funds (DD) and Village Fund Allocations (ADD), is needed to prevent corrupt practices.Purposes of The Devotion: This community service is carried out through legal counseling activities that introduce anti-corruption values to high school students and village financial management to village government staff and the community to instill integrity and prevent corrupt behavior.Method of The Devotion: The method used is as follows: First, we collected initial data to determine the needs of the Mamala Village community. Second, we processed this initial data and then presented it through Legal Counseling activities. Third, we provided Legal Counseling to both Muhammadiyah Senior High School students and village officials and the Mamala Village community. Fourth, we collected final data to evaluate the Legal Counseling we conducted.Results Main Findings of the Devotion: The students gained an understanding of anti-corruption values and their implementation in their lives as students at school. Likewise, village government staff and the community become aware of village financial planning and how to make good financial accountability reports so as to avoid corrupt behavior.